Parameterized Hilbert-Type Integral Inequalities in the Whole Plane - Qiliang Huang; Shanhe Wu; Bicheng Yang (The Scientific World Journal)
By the use of the way of real analysis, we estimate the weight functions and give some new Hilbert-type integral inequalities in the whole plane with nonhomogeneous kernels and multiparameters. The constant factors related to the hypergeometric function and the beta function are proved to be the best possible. We also consider the equivalent forms, the reverses, and some particular cases in the homogeneous kernels.